Analysis Of Effect Size Company, Profitability, And Leverage Against Social Responsibility Disclosure Of Listed Mining Industry In Indonesia Stock Exchange Period 2009-2012 - Haninun HANINUN; Nurdiawansyah NURDIAWANSYAH (Universitas Bandar Lampung (UBL), 2014)
This study aims to identify and analyze the effect of firm size , profitability and leverage on the disclosure of social responsibility in the mining industry sectors listed on the Indonesia Stock Exchange 2009-2012 . The hypothesis was first put forward in a positive effect of firm size on corporate social responsibility disclosure , the second hypothesis is the positive effect on the profitability of social responsibility disclosure , the third hypothesis is the negative effect of leverage on corporate social responsibility disclosure . Measurement of corporate social responsibility is based on the category of the Global Reporting Index (GRI) is seen in the companys annual financial statements.The sample in this study is that the mining industry is listed in Indonesia Stock Exchange 2009-2012. Sampling using purposive sampling in order to obtain a total sample of 16 mining companies that meet the criteria of the study sample set. Company size is measured by total assets , profitability measured by Return on Assets ( ROA ) , and leverage is measured using a Debt Equity Ratio ( DER ) . The technique of data analysis done with the classical assumption, hypothesis testing using multiple linear regression analysis using SPSS 18.0 for windows.The results showed that in partial firm size , profitability has positive influence on social responsibility disclosure in the mining industry are listed in the Indonesia Stock Exchange , while the variable leverage negatively affects social responsibility disclosure in the mining industry are listed in the Indonesia Stock Exchange.